The characterization of extracellular vesicles-derived microRNAs in Thai malaria patients - Ketprasit, N; Cheng, IS; Deutsch, F; Tran, N; Imwong, M; Combes, V; Palasuwan, D (BioMed Central, 2020)
Background Extracellular vesicles (EVs) have been broadly studied in malaria for nearly a decade. These vesicles carry various functional biomolecules including RNA families such as microRNAs (miRNA). These EVs-derived microRNAs have numerous roles in host-parasite interactions and are considered promising biomarkers for disease severity. However, this field lacks clinical studies of malaria-infected samples. In this study, EV specific miRNAs were isolated from the plasma of patients from Thailand infected with Plasmodium vivax and Plasmodium falciparum. In addition, it is postulated that these miRNAs were differentially expressed in these groups of patients and had a role in disease onset through the regulation of specific target genes. Methods EVs were purified from the plasma of Thai P. vivax-infected patients (n = 19), P. falciparum-infected patients (n = 18) and uninfected individuals (n = 20). EV-derived miRNAs were then prepared and abundance of hsa-miR-15b-5p, hsa-miR-16-5p, hsa-let-7a-5p and hsa-miR-150-5p was assessed in these samples. Quantitative polymerase chain reaction was performed, and relative expression of each miRNA was calculated using hsa-miR-451a as endogenous control. Then, the targets of up-regulated miRNAs and relevant pathways were predicted by using bioinformatics. Receiver Operating Characteristic with Area under the Curve (AUC) was then calculated to assess their diagnostic potential. Results The relative expression of hsa-miR-150-5p and hsa-miR-15b-5p was higher in P. vivax-infected patients compared to uninfected individuals, but hsa-let-7a-5p was up-regulated in both P. vivax-infected patients and P. falciparum-infected patients. Bioinformatic analysis revealed that these miRNAs might regulate genes involved in the malaria pathway including the adherens junction and the transforming growth factor-β pathways. All up-regulated miRNAs could potentially be used as disease biomarkers as determined by AUC; however, the sensitivity and specificity require further investigation. Conclusion An upregulation of hsa-miR-150-5p and hsa-miR-15b-5p was observed in P. vivax-infected patients while hsa-let-7a-5p was up-regulated in both P. vivax-infected and P. falciparum-infected patients. These findings will require further validation in larger cohort groups of malaria patients to fully understand the contribution of these EVs miRNAs to malaria detection and biology.